(untitled) (Balneo and PRM Research Journal, 2024)
Balneotherapy, treating diseases by bathing in mineral-rich waters and mud, has a long historical application across various cultures. Despite its widespread use, comprehensive studies on its biological impacts are scant, particularly in quantifying effects at the cellular and systemic levels. This study aims to rigorously investigate the biological effects of therapeutic mud and mineral waters, providing a scientific basis for their clinical application. We focused on elucidating the mechanisms behind the observed therapeutic effects and determining these natural resources’ safety profiles. Employing a dual approach, we conducted both in vitro and in vivo studies. For the in vitro experiments, human fibroblast cells were treated with different concentrations of mud extracts to assess cytotoxicity, proliferation, and apoptosis pathways. For the in vivo assessments, Wistar rats were exposed to mud and mineral water treatments, with subsequent evaluations of biochemical markers in blood and urine indicative of systemic physiological changes. Our findings reveal that mud extracts exert a dose-dependent influence on cell viability, with low concentrations promoting cellular proliferation while higher concentrations induce apoptosis. In vivo treatments demonstrated significant modulation of inflammatory markers and oxidative stress parameters without evident systemic toxicity. The therapeutic mud and mineral waters demonstrate pronounced biological effects, enhancing cellular health and modulating systemic physiological responses without adverse side effects.